Zmynd11 is essential for neurogenesis by coordinating H3K36me3 modification of Epha2 and PI3K signaling pathway - Xu Yang; Lan Li; Wenzheng Qu; Xuejun Cheng; Jinyu Zhang; Yan Sun; Suxiao Liu; Guoping Peng; Rui Zheng; Xuekun Li (Cell & Bioscience)
Abstract 10p15.3 deletion syndrome is caused by the deficiency of MYND-type zinc finger domain-containing protein 11 (ZMYND11) and featured by global developmental delay, intellectual disability, behavioral abnormalities, etc. Although the roles of Zmynd11 is intensively studied in cancer, the function and associated mechanisms of Zmynd11 in neurodevelopment remain largely unknown. Here, we show that Zmynd11 displays abundant and dynamic expression pattern during embryonic neurodevelopment. Zmynd11 deficiency impairs embryonic neurogenesis and neurodevelopment in vitro and in vivo, and inhibits morphological maturation of neurons. Mechanistically, Zmynd11 deficiency leads to decreased Epha2 and disrupts PI3K signaling pathway. Under Zmynd11 deficient condition, H3K36me3 modification on Epha2 promoter abnormally increases and the binding of RNA polymerase II decreases. The restoration of PI3K signaling pathway by exogenous Epha2 can rescue aberrant neurogenesis induced by Zmynd11 depletion in vitro and in vivo. Collectively, our study reveals the essential function of Zmynd11 in neurogenesis via coordinating H3K36me3 modification of Epha2 and PI3K signaling pathway.